2012
DOI: 10.2134/jeq2012.0116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Existing Roadside Swales with Engineered Filter Soil: II. Treatment Efficiency and in situ Mobilization in Soil Columns

Abstract: Use of roadside infiltration systems using engineered filter soil for optimized treatment has been common practice in Germany for decades, but little documentation is available regarding their long-term treatment performance. Here we present the results of laboratory leaching experiments with intact soil columns (15 cm i.d., 25-30 cm length) collected from two German roadside infiltration swales constructed in 1997. The columns were irrigated with synthetic solutions of unpolluted or polluted (dissolved heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…It seems like the filter soil is removing particulate P while at the same time leaching dissolved P. As for SS and OC, this points to mobilization of the internal P-pool in the filter soil, as was also shown in the studies by Ingvertsen et al [16]. In parallel with this, swale-trenches leached more particle-bound P than the low SS-leaching curb extensions, where P was mostly in dissolved form, probably reflecting the higher plant-available P in the landfill soil.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…It seems like the filter soil is removing particulate P while at the same time leaching dissolved P. As for SS and OC, this points to mobilization of the internal P-pool in the filter soil, as was also shown in the studies by Ingvertsen et al [16]. In parallel with this, swale-trenches leached more particle-bound P than the low SS-leaching curb extensions, where P was mostly in dissolved form, probably reflecting the higher plant-available P in the landfill soil.…”
Section: Discussionsupporting
confidence: 73%
“…When comparing the soil from swale-trenches and curb extensions it is observed that the local soil in the swale-trenches was leaching more OC than the landfill soil in curb-extensions, similar to what was observed for SS. Leaching of organic matter was also observed by [16] from German filter soil, 15 years old, but even young systems like the ones monitored here leach organic matter. Organic matter is not a pollutant as such, but can be a source of P and complex metals such as Cu and cause leaching of these e.g., [39,40].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations